Growth mindset in high school mathematics: A review of the literature since 2007 - Micah Stohlmann; Yichen Yang (Journal of Pedagogical Research, 2024)
Growth mindset has received more focus in schools in the past fifteen years as a possible way to improve various educational outcomes. There are important possible benefits if students believe in the malleability of intelligence and the potential to improve in ability and various human qualities. Students with growth mindsets set self-improvement as achievement goals, use all of their resources, seek feedback, attribute failure to something that is under their control, and work harder when faced with setbacks. For mathematics, these beliefs and outcomes of a growth mindset are especially important as students may view mathematics as too difficult and a barrier or detterent to a possible career. The notion that only some students can do well in mathematics is important to counter. The purpose of this article to review the research on growth mindset in high school mathematics education since 2007. Directions for future research are discussed including the importance of teachers in growth mindset interventions and students developing growth mindsets through having successful mathematics learning experiences.